A Decision Support System for Evaluation of Municipal Mobile Solid Waste Systems Within the Framework of Sustainability - Yildiz, Aslihan; Alp, Selcuk; Ozkan, Coskun; Kocatas, Fatih (SPRINGER INTERNATIONAL PUBLISHING AG, 2024)
Municipalities, which contribute greatly to the development of cities, also play an active role in solid waste management (SWM). Municipalities that aim to maintain SWM effectively must carry out the collection, transfer, storage, disposal, or recycling processes. Municipalities' efforts to be sustainable towards solid waste are becoming more prominent. Evaluating the suitability of municipal solid waste systems is extremely critical in terms of both the service performance of the municipalities and the satisfaction of the residents. In the study, the criteria required for the sustainable performance of Municipal Solid Waste Management (MSWM) systems are determined. Studies in the literature regarding the problem are included. In light of these studies, sustainability criteria are determined for the problem. In addition to the economic, social, and environmental criteria, which are expressed as the triple bottom of sustainability, the Risk criterion is also added to the study. Thus, a more realistic approach to the evaluation of MSWMis presented.
Keywords: Waste Management; Sustainability; Multi Criteria Decision; BEST-WORST; SELECTION; COLLECTION; MANAGEMENT; Computer Science